CHOLESTEROL LEVELS BEFORE AND AFTER CONSUMING SAUSAGE - Margareta Haiti; Lidwina Septie Christyawardani; Yulia Dewi Rahmawati (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Cholesterol is a component of fat forming yellow and in the form of wax which is produced by the liver. One of the foods that can increase cholesterol levels is meat sausage. These food ingredients, if consumed in excess amounts, will increase fat levels in the body, which in turn will increase total cholesterol levels in the blood (hypercholesterolemia). In this millennial era, many foods are produced fast using raw materials from processed meat, one of which is sausage. Sausage is one of the foods that are high in fat, so there will be an increase in fat levels in the body when a person consumes 50 grams of sausage (half a portion). Methods: This research uses analytic / inferential research, namely pre-experiment. There were 20 subjects used.The average (mean) blood cholesterol level before consuming sausage was 203.51 mg / dL and the mean (mean) blood cholesterol level after consuming sausage was 207.67 mg / dL. Furthermore, the results obtained after statistical testing using the paired T-Test, namely p value = 0.056, meaning that there was no significant difference in cholesterol levels before and 2 hours after consuming sausages.In this study it can be concluded that there is no significant difference in cholesterol levels before and 2 hours after consuming 75 grams of sausage (1 serving).